THE RELATIONSHIP OF MOTHER'S KNOWLEDGE WITH THE EVENT OF THE PERSISTENCE OF CHILD IN CLASS II AND III AT SDN 12 KOTA BANDA - Elfi Zahara (Journal Dental Health, 2022)
Abstract This research is analytic with a cross sectional design, carried out on 6 to 10 September 2021. The population in this study was all second and third grade students at SDN 12 Kota totaling 58 Mother's knowledge is the closest person to the child in health care has a significant influence significant effect on the attitudes and behavior of children. Based on the initial data from the examination conducted on 15 students of SDN 12 Banda Aceh City, it was found that 8 students had persistent teeth. The purpose of this study was to determine the relationship between mother's knowledge and persistence in grade II and III children at SDN 12 Banda Aceh City. This research is analytic with a cross sectional design, carried out on September 6 to 10, 2021. The population in this study was all students in grades II and III at SDN 12 Kota, totaling 58 students. The sample in this study used a total population of 58 students. Collecting data by means of dental examinations on students and interviews with students' mothers using questionnaires. This analysis was tested statistically using the SPSS program with a chi-square test with 0.05. The results showed that students who had dominant tooth persistence had mothers with poor knowledge as many as 28 students (84.8%) while children who did not have dominant tooth persistence had mothers with good knowledge as many as 18 students (72%). -square value obtained is p = 0.000 (p <0.005). There is a relationship between maternal knowledge and the incidence of persistence in grade II and III students at SDN 12 Banda Aceh. Banda Aceh students. The sample in this study used a total population of 58 students. Collecting data by means of dental examinations on students and interviews with students' mothers using questionnaires. This analysis was tested statistically using the SPSS program with a chi-square test with 0.05. The results showed that students who had dominant tooth persistence had mothers with poor knowledge as many as 28 students (84. 8%) while children who did not have dominant tooth persistence had mothers with good knowledge as many as 18 students (72%). -square value obtained is p = 0.000 (p <0.005). There is a relationship between maternal knowledge and the incidence of persistence in grade II and III students at SDN 12 Banda Aceh. Banda Aceh Keywords: Dental and Oral Health Maintenance, Leaflet, Knowledge